THE INFLUENCE OF CHARACTER EDUCATION, LEARNING MOTIVATION ON THE COMPETENCY AND PERFORMANCE OF PUSDIKLEK GRADUATES IN CARRYING OUT THE MAIN DUTIES OF THE INDONESIAN NAVY - Nordi; C Imron; Adi Bandono; Achmad Sumartoni (STTAL POSTGRADUATE - INTERNATIONAL CONFERENCE, 2024)
In carrying out the main tasks of the Indonesian Navy, professional and reliable personnel of the Indonesian Navy's defense equipment are needed. This can be done by improving the quality of character education and learning motivation, especially at the Pusdiklek Kodikdukum Kodiklatal which is responsible for preparing marine soldiers of the electronics corps who are moral, professional and have mastered the technology in the fields of electronics and informatics. This study examines the influence of character education, learning motivation and competence on the performance of Pusdiklek graduates, using the Structural Equation Modeling (SEM) method. This study aims to test the significance of the influence of character education, learning motivation both directly and indirectly through competence on performance. The results of the study indicate that character education has a direct and significant effect on competence with an estimated path coefficient of 0.415; learning motivation has a direct and significant effect on competence with an estimated path coefficient of 0.522; competence has a direct and significant effect on performance of 0.359; character education has a direct and significant effect on performance with an estimated path coefficient of 0.288; learning motivation has a direct and significant effect on performance with an estimated path coefficient of 0.454; character education has a significant influence on the performance of soldiers graduating from Pusdiklek through competence (as a mediating variable) with a mediation coefficient of 0.149; and learning motivation has a significant influence on the performance of soldiers graduating from Pusdiklek through competence (as a mediating variable) with a mediation coefficient of 0.187. All hypotheses proposed are accepted, indicating that increasing character education, learning motivation and competence can have a significant influence on improving the performance of Pusdiklek graduates.